A new species of Ornebius Guérin-Méneville, 1844 from East China (Orthoptera: Mogoplistidae: Mogoplistinae) - He, Zhuqing; Lu, Hui; Liu, Yuqing; Li, Kai (Zootaxa, 2017)
A new species, Ornebius polycomus sp. nov., is described from East China. There are distinct differences with known species in morphology, songs and molecular evidence. The type specimens are deposited in East China Normal University, Biology of History Museum (ECNU).